Investigating the impact of Eko Excel tablets on primary school mathematics performance: A quasi-experimental study in Nigeria - Nasrudeen Ayinde Malik; Semiu Olawale Makinde; Khalid Saddiq (Ricerche di Pedagogia e Didattica)
This research investigated the impact of utilising the Tablet on the Primary school pupils’ performance in mathematics. Three hypotheses guided the study, and the quasi-experimental design involving pre-test and post-test was used. 150 primary four pupils from schools in Lagos state participated in the study. Mathematics Achievement Test (MAT) was used for data collection. This assessment tool exhibited a satisfactory level of reliability, indicated by a coefficient of 0.73. The hypotheses were scrutinized through analysis of covariance (ANCOVA). The results indicated a substantial enhancement in mathematics scores when employing Eko Excel Tablets in contrast to conventional teaching approach. Gender had no discernible impact on mathematics performance among pupils using these tablets. Suggestions were made to oversee the integration of tablets in school curricula by the Lagos State Universal Basic Education Board (LASUBEB) to foster improved academic outcomes among pupils.